Classical Music Concert Attendance and Older Adults: A Goal-Directed Approach. (1st April 2016) - Tong, Eudora; White, Christopher James; Fry, Tim
Abstract: Older adults are a lucrative consumer market. In finance and health markets, considerable attention has been devoted to understanding their preferences and the factors that influence their decisions and behaviors. In a classical music concert context, older adults are extremely important; despite accounting for half of all attendees in most countries, little theory-based research explains classical music attendance in general and by these older adults in particular. Using the Model of Goal Directed Behavior (MGB) as a foundation, we collected data from attendees and propose a revised model to capture the behavioral processes involved in the formation of positive word of mouth communication among these consumers. A modified version of the MGB predicted 57% of the variance in word of mouth and the model/data fit statistics were acceptable suggesting that the revised MGB is a robust and viable option when considering leisure behavior or engagement.